Clinical and Genomic Evaluation of 207 Genetic Myopathies in the Indian Subcontinent - Chakravorty, Samya; Nallamilli, Babi Ramesh Reddy; Khadilkar, Satish Vasant; Singla, Madhu Bala; Bhutada, Ashish; Dastur, Rashna; Gaitonde, Pradnya Satish; Rufibach, Laura E; Gloster, Logan; Hegde, Madhuri (Frontiers in Neurology, 2020)
Objective Inherited myopathies comprise more than 200 different individually rare disease-subtypes but when combined together have a high prevalence of 1 in 6000 individuals across the world. Our goal was to determine for the first time the clinical- and gene-variant spectrum of genetic myopathies in a substantial cohort study of the Indian subcontinent. Methods In this cohort-study, we performed the first large clinical exome sequencing (ES) study with phenotype correlation on 207 clinically well-characterized inherited myopathy-suspected patients from the Indian subcontinent with diverse ethnicities. Results Clinical-correlation driven definitive molecular diagnosis was established in 49% (101 cases; 95% CI, 42%-56%) of patients with the major contributing pathogenicity in either of three genes, GNE (28%; GNE-myopathy), DYSF (25%; Dysferlinopathy) and CAPN3 (19%; Calpainopathy). We identified 65 variant alleles comprising 37 unique variants in these three major genes. 78% of the DYSF patients were homozygous for the detected pathogenic variant suggesting the need for carrier-testing for autosomal-recessive disorders like Dysferlinopathy that are common in India. We describe the observed clinical spectrum of myopathies including uncommon and rare subtypes in India: Sarcoglycanopathies (SGCA/B/D/G), Collagenopathy (COL6A1/2/3), Anoctaminopathy (ANO5), telethoninopathy (TCAP), Pompe-disease (GAA), Myoadenylate-deaminase-deficiency-myopathy (AMPD1), myotilinopathy (MYOT), laminopathy (LMNA), HSP40-proteinopathy (DNAJB6), Emery-Dreifuss-muscular-dystrophy (EMD), Filaminopathy (FLNC), TRIM32-proteinopathy (TRIM32), POMT1-proteinopathy (POMT1), and Merosin-deficiency-congenital-muscular-dystrophy-type-1 (LAMA2). 13 Patients harbored pathogenic variants in >1 gene and had unusual clinical features suggesting a possible role of synergistic-heterozygosity / digenic-contribution to disease presentation and progression. Conclusions Application of clinically-correlated ES to myopathy diagnosis has improved our understanding of the clinical and genetic spectrum of different subtypes and their overlaps in Indian patients. This, in turn, will enhance the global gene-variant-disease databases by including data from developing countries/continents for more efficient clinically-driven molecular diagnostics.